Physicochemical status of Nwanedi river water, and its influence on the metabolome of river-irrigated tomato leaves - Leornard Ntanganedzeni Musweswe; Chimdi Mang Kalu; Khayalethu Ntushelo (PLoS ONE, 2026)
Contaminated water used for irrigation has been reported to trigger metabolic and physiological changes in plants. This study assessed the physicochemical status, pH, total dissolved solids (TDS), electrical conductivity (EC), salinity (SAL), and metals of Nwanedi River water and its influence on the primary metabolome of disordered tomato leaves (a physiological condition) irrigated with the Nwanedi River water. The physicochemical properties of water from Nwanedi River were measured by a multi-probe field meter, metal concentration by Inductively Coupled Optical Emission Spectrometer (ICP-OES), and primary metabolite profiling of disordered leaves done using LCMS-8040 triple quadrupole mass spectrometer. The pH, EC, TDS, Cd and Pb of river water were above the stipulated standards for irrigation purposes. Levels of hypoxanthine in tomato leaves were influenced negatively by pH (r = −0.91), TDS (r = −0.93), EC (r = −0.93), and SAL (r = −0.95) as revealed by Pearson correlation. Other metabolite quantities significantly swayed by the water’s condition were histamine, thymine, 4-hydroxyproline, acetylcarnitine and carnosine. The correlations between primary metabolites in the disordered leaves and the physicochemical parameters could indicate mitigation and adaptation mechanisms of the tomato plant.